2019
DOI: 10.1097/ajp.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Level of Catastrophizing and Mental Health Comorbidity in Individuals With Whiplash Injuries

Abstract: Objectives: Pain catastrophizing has been shown to be correlated with measures of mental health problems such as depression and post-traumatic stress disorder (PTSD). However, the clinical implications of findings reported to date remain unclear. To date, no study has been conducted to determine meaningful cut-scores on measures of catastrophizing indicative of the heightened risk of mental health comorbidity. One objective of the present study was to identify the cut-score on the Pain Catastrophiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The question of whether pain catastrophizing has a direct effect on depression continues to be debated. The results of Paré et al's study, which showed high correlations between pain catastrophizing and depression [34] and Nicholas et al's study, which found that depression correlated more with cognitive variables than pain itself, underscored the direct effects of pain catastrophizing [35]. In contrast, Hülsebusch et al found that pain catastrophizing had an indirect effect on depression through helplessness/hopelessness, and this observation is similar to the findings of this study [36].…”
Section: Discussionsupporting
confidence: 86%
“…The question of whether pain catastrophizing has a direct effect on depression continues to be debated. The results of Paré et al's study, which showed high correlations between pain catastrophizing and depression [34] and Nicholas et al's study, which found that depression correlated more with cognitive variables than pain itself, underscored the direct effects of pain catastrophizing [35]. In contrast, Hülsebusch et al found that pain catastrophizing had an indirect effect on depression through helplessness/hopelessness, and this observation is similar to the findings of this study [36].…”
Section: Discussionsupporting
confidence: 86%
“… 8 For individuals with mental health conditions, the sudden onset of new symptoms can lead to catastrophic thinking. 31 , 83 According to Ellis, 31 catastrophic thinking is the tendency to magnify a perceived threat and overestimate the seriousness of its potential consequences. Catastrophizing leads to avoidance and safety-seeking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Significant pain may also be associated with depression. [ 17 ] The SF-MPQ-2 is a validated tool that is increasingly being used to assess pain. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%